The landscape of small cell lung cancer metastases: Organ specificity and timing. Issue 6 (3rd February 2021) - Megyesfalvi, Zsolt; Tallosy, Bernadett; Pipek, Orsolya; Fillinger, Janos; Lang, Christian; Klikovits, Thomas; Schwendenwein, Anna; Hoda, Mir Alireza; Renyi‐Vamos, Ferenc; Laszlo, Viktoria; Rezeli, Melinda; Moldvay, Judit; et al.
Abstract: Background: Early metastasis is a hallmark of small cell lung cancer (SCLC). However, the mechanisms and resulting patterns of SCLC dissemination are unclear. Our aim was thus to investigate the organ specificity and timing of blood‐borne metastases in a comprehensive large cohort of SCLC patients. Methods: In this retrospective non‐interventional cross‐sectional study of 1009 Caucasian SCLC patients, we investigated the correlation between the distinct locations of the primary tumor and metastatic sites. Results: The onset of bone ( p  < 0.001), brain ( p  < 0.001), and pericardial ( p = 0.02) metastases were late events, whereas adrenal gland ( p = 0.005) and liver ( p  < 0.001) metastases occurred earlier. No significant difference was found in the distribution of early versus late metastases when comparing central and peripheral primary tumors. Patients with bone metastases had a higher than expected likelihood of having liver metastases, while brain metastases tended to appear together with adrenal gland metastases. Pleural and both lung and pericardial metastases also tended to co‐metastasize together more frequently than expected if metastatic events occurred independently. Notably, patients with central primary tumors had decreased median overall survival (OS) compared to those with peripheral tumors, although this tendency does not appear to be significant ( p = 0.072). Conclusion: Our results are suggestive for particular site‐ and sequence‐specific metastasis patterns in human SCLC. SCLC bone metastases tend to appear together with liver metastases, while brain metastases occur together with adrenal gland metastases. Better understanding of metastasis distribution patterns might help to improve the diagnosis and therapeutic decision‐making in SCLC patients. Abstract : In this study, our aim was to examine the organ specificity and timing of blood‐borne metastases in a comprehensive large cohort of Caucasian SCLC patients ( n =1009). We report here that the onset of bone, brain, and pericardial metastases are late events, whereas adrenal gland and liver metastases occur earlier during tumor progression. We also show that several metastatic sites, such as bone and liver, and brain and adrenal gland intend to co‐metastasize preferentially. Of note, however, no significant associations were observed with regards to the timing and organ preference of distant metastases when comparing central and peripheral primary tumors.